Eosinophilic Fascitis: A Rare Fibrosing Disorder - Paudyal, Buddhi; Gyawalee, M; Sigdel, K (Kathmandu University Medical Journal, 2013)
Eosinophilic fasciitis is a rare systemic disease characterized by inflammatory thickening of the skin and underlying fascia, peripheral eosinophilia, elevated inflammatory markers and typical biopsy findings. Internal organ involvement is rare unlike in other fibrosing disorders. Though this is usually a benign disease, it is often difficult to diagnose and the course may also be variable. Glucocorticoids are the mainstay of therapy, but in many cases steroid sparing immunosuppressive drugs are required particularly if the diseases has protracted course. The author reports a typical case of this rare disorder which could well be a first report from Nepal. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 73-75 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8025